The Effectiveness Of Padlet Aplication On Teaching Writing Descriptive Text In Eleventh Grade At SMA N 1 Girsang Sipangan Bolon - Hotsita Simbolon; Kammer Tuahman Sipayung; Nenni Triana Sinaga; Tutiarny Naibaho (Universitas Pahlawan Tuanku Tambusai, 2023)
This research is aimed to find out the effectiveness of Padlet Aplication on Teaching Writing Descriptive Text in Eleventh Grade at SMAN 1 Girsang Sipanganbolon. The research design of this study is True-experimental design. The were chosen as the sample of this study with the total number 60 students. In this research, the researcher took two class as the sample that is eleventh grade class IIS3 and IIS4 of SMA N 1 Girsang Sipanganbolon. The instrument used in this thesis was writing test. In collecting the data, the writer used pre-test and post-test. Before conducting post-test, the writer gave treatment in experimental class and used convensional teaching in control class. In experimental class given pre-test before being given treatment, after being given treatment then gives post-test. Then, in control class given pre-test , then given conventional teaching then gives post-test. After getting enough data, the researcher calculated the data using t-test formula. The result showed that the post-test score in experimental class was higher than the post-test scores in control class. The finding showed that Padlet significantly effect on the students writing ability. There was an enhancement of the students number score. The mean score of the post-test in experimental class was 72 and the post-test in control class was 66. The data analysis showed that t-count was 3,83 and t-table was 2,045. The data can be stated that t-test was higher than t-table 3,83>2,045. The data showed that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.